Scalar Effects in Ground Slate Technology and the Adaptive Consequences for Circumpolar Maritime Hunter-Gatherers - Jørgensen, Erlend Kirkeng (Journal of Archaeological Method and Theory, 2020)
Ground slate technology is a trademark of circumpolar hunter-gatherers occupying coastal ecotones. However, a causal framework for explaining what drives the apparent adaptive success of slate technology is lacking. Attempting to remedy this, the current paper provides the first palaeodemographic and environmentally informed review of a maritime slate complex. Employing what is arguably the best documented and contextually controlled slate industry in Holocene Eurasia as a high-resolution case study (the Arctic Norwegian slate industry), the system components of demography, ecology and technology are integrated to get at (1) why slate technology appears to be a particular maritime success, (2) what causal contribution slate technology makes to population-scale adaptive success, (3) why slate technology was eventually abandoned. Based on extensive empirical investigations, the results demonstrate synchronous changes in population size, maritime intensification and the use of slate technologies. It is suggested that the mechanism responsible for this correspondence is that the slate industry facilitated a heightened adaptive success, reinforcing population growth and maritime intensification. Technological results indicate that superior properties for standardization make the slate technology ideal for establishing a scale economy in maritime resource exploitation when surpassing critical thresholds in population packing. Causal modelling demonstrates that, under particular demographic and ecological conditions, the scalar properties of slate technologies can offset high- and density-dependent start-up costs, by increasing return rates and reducing handling costs of hunting/processing of marine resources. Satisfying all criteria for tool “efficiency”, it is concluded that slate industries have causal efficacy as an “enabling technology” in circumpolar, maritime settings.